PENGARUH KEPRIBADIAN GURU DAN PROFESIONALISME GURU TERHADAP PRESTASI BELAJAR SISWA KELAS X SMA NEGERI 2 PEMATANG SIANTAR - Muammar Rinaldi; Nanda Fridani (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
The This research was conducted to investigate whether there is an influence of teacher personality and teacher professionalism on student achievement in tenth-grade IPS 2 students of SMA Negeri Pematang Siantar. The population in this study were all students of tenth-grade IPS SMA Negeri 2 Pematang Siantar, totaling 188 people. The sampling technique in this study used a random sampling method of 64 students. Data collection techniques used were observation, questionnaires, and documentation. The validity test for item questionnaire analysis used the product-moment correlation formula, and the reliability was calculated using the Cronbach alpha formula. Data analysis techniques used were multiple linear regression, t-test, F test and test determination (R2). The value of determination (R2), the contribution of teacher personality variables and teacher professionalism to student achievement, is 14.7%. The rest is influenced by other variables that are outside the analysis of this study. It can be concluded that the teacher's personality has a positive and significant influence on student achievement. Whereas teacher professionalism did not have a positive and significant influence on student achievement in tenth-grade students IPS SMA Negeri 2 Pematang Siantar.